The Attitude of Junior High School Students toward The Early Marriage - Pipitcahyani, Tatarini Ika; Chahyaya, Iiv Hayyu (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-